POLA KOMUNIKASI DAKWAH INKLUSIF UNTUK MASYARAKAT MULTIKULTURAL: PERSPEKTIF MANAJEMEN DAKWAH MODERN - Ahmadi, Mubarok; Gunarti, Tri Tami (Universitas Kiai Abdullah Faqih Gresik, 2024)
Abstract: Inclusive da'wah communication has become an urgent necessity in multicultural societies to ensure that the Islamic message of rahmatan lil 'alamin (a mercy to all creation) is universally embraced. This study aims to explore the patterns of inclusive da'wah communication through the perspective of modern da'wah management, focusing on adaptive strategies that address the challenges of cultural, linguistic, and religious diversity. Employing a qualitative approach with a case study method, this research examines the implementation of inclusive communication strategies within da'wah communities in multicultural regions of Indonesia. The findings reveal that inclusive da'wah communication requires three key elements: 1) Cultural Empathy, the ability of preachers (da’i) to understand and appreciate the local values of the community. 2) Cross-Cultural Collaboration to involves synergy between local communities and religious leaders to deliver dakwah messages contextually, and 3) Utilization of Digital Technology, serving as a medium to extend the reach of da'wah while preserving the essence of Islamic values. Furthermore, the study highlights that data-driven da'wah management approaches significantly aid in designing targeted and relevant da'wah programs tailored to community needs. In conclusion, inclusive da'wah communication not only enhances the effectiveness of da'wah in multicultural societies but also serves as a model for fostering social harmony and strengthening national identity. This research provides both theoretical and practical contributions to the advancement of modern da'wah management in the globalization era. Keyword: Dakwah Communication; Inclusivity; Multicultural Societies; Dakwah Management; Social Harmony